Bollywood - Banker, Ashok (Pocket Essentials, 2001)
This Pocket Essential explores the awe inspiring world of Bollywood up to 2001. Bombay's prolific Hindi-language film industry is more than just a giant entertainment juggernaut for 1 billion-plus Indians worldwide. It's a part of Indian culture, language, fashion and lifestyles. It's also a great bundle of contradictions and contrasts, like India itself. Thrillers, horror, murder mysteries, courtroom dramas, Hong Kong-style action gun fests, romantic comedies, soap operas, mythological costume dramas ... they're all blended with surprising skill into the musical boy-meets-girl formula of Bollywood. The results are a bizarre, overblown mixture of high concept, ethnic color, traditional values, high-pitched emotional drama, sizzling sensuality and music, always music. What's in this book? As well as an introductory essay, a selection of 25 major seminal films are examined in entertaining, intimate detail. There's also a section on the current state of the industry, the star system, film music, and a list of additional books and films that will help you enjoy and make sense of the new Hindi movie showing at your nearest multiplex.